Pengaruh Latihan Yoga Terhadap Perubahan Tekanan Darah Pada Pasien Hipertensi (Di Desa Karanganom, Kecamatan Durenan, Kabupaten Trenggalek Tahun 2018) - Solekah, Imro’atus; Rohmawati, Indah; Surtini, Surtini (JOURNAL OF MEDICAL AND HEALTH SCIENCE, 2025)
Hypertension is one of the serious health problems. Management there are 2 ways that is pharmacological and non pharmacological. Nonfarmakologis way by exercising regularly one of them yoga practice. The purpose of this study was to determine the effect of yoga practice on changes in blood pressure in Karanganom Village Durenan Trenggalek year 2018. The design of this research is Pre Experimental, with the design of "One Group Pretest-Posttest Design" .The population of this study were all patients of hypertension present in the village with purposive sampling technique in get 20 peoples samples. The data were collected on 12-17 March 2018 by observing blood pressure before being given yoga practice, after being given yoga exercises for 6 days in a row and processed with stage Editing, Coding, Scoring, and Tabulating stage and analyzed using Paired t- test. From the results of the study showed that before given the prectice of yoga the avarage systolic blood pressure is 150,75 mmHg and diastolic 93 mmHg.After being given an avarage yoga practice systolic blood pressure is 147 mmHg and diastolic 90 mmHg. Test Paired t-test results obtained Pvalue systolic blood pressure that is 0,012<0,05 and Pvalue at diastolic blood pressure that is 0,014<0,05 (ρ <0,05 then H0 is rejected and Hı accepted). This means that there is a statistically significant influence of yoga practice on changes in blood pressure (systolic and diatolic) in hypertensive patients in Karanganom Durenan Trenggalek Village. Yoga exercises one of the physical activities that can overcome hypertension by working to reduce the rhythm of the body and stabilize the heartbeat, lighten the heart and maximize the blood circulation so that blood pressure can be stable or decreased. So it is important for hypertensive patients to do regular physical exercise.